(untitled) (Моделювання, керування та інформаційні технології, 2023)
This article explores the application of the V model, a structured software development and testing framework, to air defense systems. The V model’s sequential approach aligns development and testing phases, promoting comprehensive verification and validation. The article delineates the adaptation of the V model to air defense systems, encompassing both verification and validation activities. Verification ensures adherence to design and requirements, while validation assesses system alignment with user needs. The article underscores the benefits of early issue identification, higher-quality software, and improved system performance through the V model’s systematic approach.